Researchers` perspectives on adverse event reporting in resistance training trials: a qualitative study - El-Kotob, R.; Pagcanlungan, J. R.; Craven, B. C.; Sherrington, C.; Mourtzakis, M.; Giangregorio, L. M. (Applied Physiology, Nutrition, and Metabolism, 2022)
The objectives of our study were to understand researchers' current practices and perspectives on adverse event (AE) reporting in clinical trials of resistance training (RT) and to identify barriers and facilitators of AE reporting. We conducted web conference or telephone-based one-on-one semistructured interviews with 14 researchers who have published RT studies. We audio-recorded and transcribed the interviews and analyzed the data using the thematic framework method. Four themes were identified: (1) researchers lack guidance and/or motivation for rigorous AE reporting; (2) researchers who undertake AE reporting educate and value participants, use trained personnel, and implement standardized guidelines; (3) suboptimal implementation of existing AE reporting standards and the perception that available guidelines do not apply to exercise trials; and (4) acceptability and feasibility of an exercise-specific guide for AE reporting depend on its content and format. In conclusion, AE reporting methods in the field of exercise science do not align with best practice. Strategies to reduce inconsistent and suboptimal AE reporting in RT trials are urgently needed and could be based on the barriers and facilitators identified in this study.